The effect of L-theanine supplementation on the immune system of athletes exposed to strenuous physical exercise - Juszkiewicz, A.; Glapa, A.; Basta, P.; Petriczko, E.; Zolnowski, K.; Machalinski, B.; Trzeciak, J.; Luczkowska, K.; Skarpanska-Stejnborn, A. (Journal of the International Society of Sports Nutrition, 2019)
Background: The aim of this study was to analyze the response of selected components of the immune system in rowers to maximal physical exercise, and to verify if this response could be modulated by supplementation with L-theanine. Method: The double-blind study included 20 members of the Polish Rowing Team. The subjects were randomly assigned to the supplemented group (n = 10), receiving 150 mg of L-theanine extract for 6 weeks, or to the placebo group (n = 10). The participants performed a 2000-m test on a rowing ergometer at the beginning (1st examination) and at the end of the supplementation period (2nd examination). Blood samples were obtained from the antecubital vein before each exercise test, 1 min after completing the test, and after a 24-h recovery. Subpopulations of T regulatory lymphocytes (Tregs) (CD4+/CD25+/CD127-), cytotoxic lymphocytes (CTLs) (CD8+/TCRaß+), natural killer (NK) cells (CD3-/CD16+/CD56+) and TCRd -positive (Td ) cells were determined by means of flow cytometry. The levels of interleukin 2 (IL-2), interleukin 4 (IL-4), interleukin 10 (IL-10), interferon gamma (INF- ) and total antioxidant capacity (TAC) were determined with commercially available diagnostic kits. Results: Supplementation with L-theanine contributed to a significant post-exercise decrease in IL-10 concentration, which was reflected by higher values of IL-2 to IL-10 and IFN- to IL-10 ratios. Moreover, a significant post-recovery decrease in CTL count, Treg to NK and Treg to CTL ratios was observed in the supplemented group. Conclusion: Despite the decrease in the number of some cytotoxic cells (CTLs) and an increase in the proportion of Tregs to CTLs, supplementation with LTE seems to exert a beneficial effect on a disrupted Th1/Th2 balance in elite athletes, as shown by the decrease in IL-10 concentration.